Functionalized polyacrylonitrile‐nanofiber based immunosensor for Vibrio cholerae detection. Issue 44 (6th August 2016) - Gupta, Pramod K.; Gupta, A.; Dhakate, S. R.; Khan, Zishan H.; Solanki, Pratima R.
ABSTRACT: Polyacrylonitrile nanofibers (PANnf's) were electrospun directly onto an indium tin oxide (ITO)‐coated glass substrate. The PANnf/ITO electrode was partially hydrolyzed with an NaOH aqueous solution at ambient temperature to convert the nitrile groups of the PANnf's into carboxyl groups was confirmed by Fourier transform infrared spectroscopy. Furthermore, 1‐ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide– N ‐hydroxy succinimide chemistry was used to activate the COOH groups of PANnf's for the covalent co‐immobilization of monoclonal antibodies against Vibrio cholerae and bovine serum albumin for V. cholerae toxin detection. Structural, functional, and electrochemical studies of the PANnf/ITO electrode and BSA/Ab/PANnf/ITO immunoelectrode were performed, and found a uniform distribution of nanofibers with diameter of 325 ± 7.7% nm. The electrochemical response studies showed an improved sensing performance of the immunoelectrode with a detection of 6.25–500 ng/mL, a low limit of detection of 0.22 ng/mL, a sensitivity of 90 nA ng −1 mL cm −2, an association constant of 45.2 ng/mL, and a dissociation constant of 8 ng/mL. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44170. Abstract :